1994
DOI: 10.1093/infdis/170.3.644
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors For Invasive Fungal Infections Complicating Orthotopic Liver Transplantation

Abstract: Risk factors for invasive fungal infection in patients undergoing orthotopic liver transplantation were examined. Thirty-four of 168 transplants were complicated within 100 days after transplantation by documented invasive fungal infection (Candida species, 28 patients; mycelial fungi, 5; both Candida and Aspergillus species, 1). In the multivariate Cox proportional hazards model, three baseline and two posttransplant variables were independently significant risk factors for infection: level of creatinine (haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
194
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(212 citation statements)
references
References 22 publications
14
194
1
3
Order By: Relevance
“…6 It is thus not surprising that other liver transplant studies have also found both OR time and volume of blood transfused associated with invasive infections caused by Candida organisms. 3,[7][8][9]11,12 Among our patients with definite invasive infection, there was a high incidence (42%) of localized peritoneal candidiasis. This is a common feature of Candida infection in liver transplant recipients 5 and is uncommon in other solid-organ transplant recipients and neutropenic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It is thus not surprising that other liver transplant studies have also found both OR time and volume of blood transfused associated with invasive infections caused by Candida organisms. 3,[7][8][9]11,12 Among our patients with definite invasive infection, there was a high incidence (42%) of localized peritoneal candidiasis. This is a common feature of Candida infection in liver transplant recipients 5 and is uncommon in other solid-organ transplant recipients and neutropenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11][12] Factors reported to increase the risk for infection caused by Candida organisms include retransplantation, long operative (OR) time, days spent in the intensive care unit (ICU), use of preoperative antibiotics and steroids, duration of postoperative antibiotic therapy, high-dose steroids, urgent status, red blood cell (RBC) transfusion requirements, and concurrent bacterial infections. 3,[6][7][8][9][10] This study reviews the largest single-center pediatric experience with fungal infections after OLT to report the incidence and describe the spectrum of infection caused by Candida organisms in OLT, determine risk factors applicable to pediatric liver transplant recipients by using univariate and multivariate analysis, and comment on the therapeutic management and possible guidelines for antifungal prophylaxis in patients with infection caused by Candida organisms.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
“…Episodes of aspergillosis that developed after day 100 were considered late cases. 5 Cytomegalovirus disease was defined according to standard clinical criteria. l7 Cytomegalovirus disease was defined as a compatible picture associated with direct tissue culture or histologic evidence of invasive cytomegalovirus disease, or when cytomegalovirus viral syndrome was present.…”
Section: Study Population: Definitionsmentioning
confidence: 99%
“…22 Risk factors for IFI after OLT can be identified and include a requirement for prolonged intensive care unit (ICU) treatment postoperatively. 4,6,23 We performed a prospective audit of a strategy in which Abelcet was administered to patients requiring ICU treatment for 5 days or greater post-OLT. This was achieved by intensive mycological surveillance of patients administered Abelcet (before and during prophylaxis) followed by in vitro fungal speciation and antifungal susceptibility testing.…”
mentioning
confidence: 99%